Answer:
[tex]y-6=2\,(x-4)[/tex]
or in slope y-intercept form :
[tex]y=2x-2[/tex]
Step-by-step explanation:
The easiest way of find the answer for this is to use what is called the "point-slope" form of a line, because you are in fact given the value of the slope (m) and also a point [tex](x_0,y_0)[/tex] it goes through:
[tex]y-y_0=m\,(x-x_0)[/tex]
In our case the equation becomes:
[tex]y-y_0=m\,(x-x_0)\\y-6=2\,(x-4)\\[/tex]
This can also be written in the slope-intercept form by solving for "y" and operating to remove the parenthesis:
[tex]y-6=2\,(x-4)\\y=2x-8+6\\y=2x-2[/tex]